Mathematical Driven Model for Closed-Loop Supply Chain Network Design - Pandey A.K.; Kumar A.; Kushwaha S.; Dwivedi A.; Pratap S. (My University, 2025)
The closed-loop supply chain (CLSC) has gained popularity as a practical way to improve sustainability and resource efficiency in various industries. Unlike a linear supply chain, a CLSC adopts reverse logistics to recover, recycle, and reuse items or their components. This study creates a mathematical model for a reliable and effective CLSC model that integrates forward and reverse logistics operations to reduce costs, boost profits, and reduce environmental impact. A metaheuristic approach (Genetic Algorithm) is used to solve the model. The experimental findings show that the suggested strategy contributes in enhancing CLSC performance. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.